(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
This research aims to utilize GIS techniques to identify the morphometric characteristics of the Wadi Al-Kumel basin in Iraq, encompassing its spatial, morphological, topographical, and drainage characteristics, as well as the drainage patterns of the basin, to establish a digital morphometric information base for the basin. The research is based on the analysis of Landsat 8 (OLI) satellite images, digital elevation models (DEM), and field studies, utilizing ArcGIS Desktop 10.8 to prepare maps for drainage networks, determine waterway ranks, and calculate morphometric parameters. The data of the meteorological stations are relied upon to identify the type of climate of the region. The analytical and quantitative approaches are also relied upon to analyze and measure the morphometric variables, producing a map of the river network and classifying its ranks according to the Strehler method, and then analyzing the natural characteristics affecting the basin, including geological formations, topographic characteristics, climate, soil, and natural vegetation. The Wadi Al-Kumel basin is located in the northern and northeastern parts of Iraq within the undulating and high mountainous region between Nineveh and Dohuk Governorates. The total basin area reaches (926.29) km2 and a length of approximately (70) km. The number of river levels reaches six, varying in streams number and lengths according to their levels. The total number of basin streams reaches 3242 streams. This variation is due to the processes of their formation and origin, in addition to the variation in the environmental characteristics that compose them. There is also a variation in the topographic characteristics of the different parts of the basin due to the difference in the topography of the region.